?CASSAVA,PROTEIN AND IODINE INTERACTION IN THE THYROID STATUS OF RATS (Biological Sciences - PJSIR, 2000)
The possible synergistic role of dietary cyanide from cassava,low iodine intake and protein deficiency and/or imbalance on the thyroid status and goiter endemia in Akungba and Oke-Agbe villages in Akoko area of south-western Nigeria was investigated using rats as model. Thirty (30) weaning albino rats were fed on corn starch or cassava as the major source of carbohydrates, 3.5 and 10.0% levels of protein supplied by either casein or Amaranthus viridis and a salt mixture with or without iodine for 42 days. Cassava with a total hydrocyanic acid (HeN) content of 25 mg kg' DW did not cause growth depression when fed to rats with casein at 10% protein level. Iodine deficiency resulted in slightly higher weight gain while protein defi- ciency especially the vegetable rations caused significant growth reductions. Interaction between cassava/iodine deficiency and protein imbalance, especially in the vegetable rations, caused a significant increase in the weight of the thyroid gland when expressed as percent of body weight. Dietary cyanide caused a significant increase in serum and urinary thiocyanate levels while iodine deficiency caused a significant reduction in the plasma protein-bound iodine (PBI). These results would partially explain the goiter endemia in Akungba and Oke-Agbe villages whose nutritional status was mimicked in these experiments.